Malaysia And The Author: Face-to-face With The Challenges Of Multiculturalism - M. M, Raihanah (Penerbit Universiti Sains Malaysia (USM Press), 2009)
Multiculturalism, or the plurality of ethnicity and culture, a colonial legacy, is still a contested issue in present day postcolonial Malaysia. The lack of ethnic interaction in plural Malaya has had repercussions on various spheres of society. This paper considers the impact of Malaysia's management of diversity on the country's literary scene. The paper addresses how multiculturalism presents a challenge for Malaysian writers in English both in their choice of language and in their representation of society. The conclusion drawn from the discussion highlights that through their 'authorial-defined' social reality, Malaysian writers in English take distinct yet constructive efforts at representing the personal, communal and national needs of the people.